Fichte, Kant e l’orientarsi nel pensare - Federico Ferraguto (Revista de Filosofia, 2016)
The paper discusses Fichte’s reception of the kantian essay Was heißt: Sich im Denken zu orientiren? that Fichte employs in different phases of his thought in highlighting the specific nature of his Wissenschaftslehre respect to Kant’s critical philosophy and to identify the misunderstandings that led to psychological (Fries) and realistic (Bardili) misrepresentation of criticism. The article discusses the definition of objectivity of representations that can be formed from the transcendental point of view, that Fichte elaborates in the Wissenschaftslehre nova methodo; the possibility to derive a real object from the logic, which Fichte reflected in the Transzendentale Logik II (§ 3) and the different constitution of the object that can be configured within the transcendental context, that Fichte describes in the Einleitungsvorlesungen in die Wissenschaftlehre 1813 (§ 4).